Peran Media Audio Visual Video terhadap Motivasi Pembelajaran Peserta Didik SD/MI - Okki Demusti; Moh. Ferdi Hasan; Andi Prastowo (SAP (Susunan Artikel Pendidikan), 2023)
Technology is evolving rapidly, affecting education. One of the current impacts is the availability of audio-visual videos as learning tools to enhance student engagement. This research aims to investigate the influence of audio-visual video media on students' learning motivation. This study builds upon previous research that revealed low student motivation in learning and confirmed low interest among the students in the researcher's environment. This research was conducted in February 2023, involving a sample of 20 fourth-grade students at SD Muhammadiyah Condong Catur in Yogyakarta. The researcher collaborated with the homeroom teacher, observed classroom activities, and administered post-lesson comprehension tests. The research employed a descriptive qualitative approach, with data collection through observations, assessments of student comprehension, and documentation. The research findings demonstrate a positive and significant impact of audio-visual video media on enhancing students' learning motivation.